Different Nutritional Histories Affect the Susceptibility of Algae to Grazing. Issue 5 (28th August 2019) - Venuleo, Marianna; Giordano, Mario
Abstract : We hypothesize that algae with different cell compositions are differently perceived by their predators and consequently subjected to selective grazing. Five populations of the diatom Phaeodactylum tricornutum that differed in organic and elemental composition, but were otherwise identical, were generated by acclimation to distinct growth regimes. The different populations were then mixed in pairs and subjected to predation by either the rotifer Brachionus plicatilis or the copepod Acartia tonsa . The presence of rotifers had no impact on the ratio between any two algal populations. The presence of copepods, however, affected the ratio between algae previously acclimated to a medium containing 1 mM NH4 + and algae acclimated to 0.5 mM NO3 −, and to either a lower irradiance or a higher CO2 concentration. We discuss the possible reason for the influence of different nutritional histories on the vulnerability of algae to predators. The differential impact of grazers on the growth of algae with different nutritional histories may result from direct selective grazing (i.e., grazers can detect algae with the most palatable cell composition), alone or combined to an asymmetric utilization of the nutrients regenerated after predation by co‐existing algal populations. Our results strongly suggest that the nutritional history of algae can influence the relationships between phytoplankton and grazers and hint at the possibility that algal cell composition is potentially subject to natural selection, because it influences the probability that algae survive predation.